Sparse Array Design Using the Genetic Algorithm for Optimizing the Radiation Pattern of Linear Arrays - de Souza, Julio Cesar Eduardo [UNESP]; Prado, Vander Teixeira; Kitano, Cláudio [UNESP]; Higuti, Ricardo Tokio [UNESP] (Springer Nature, 2019)
The genetic algorithm was used to obtain sparse arrays with 8, 16, 32 and 64 transducers in a possible aperture size of 128 elements. The optimization was made by minimizing a fitness function that takes into account the mainlobe width and sidelobe levels of the array radiation pattern. The sparse arrays were used to image 11 twisted wires in a medical phantom. The sparse arrays were able to generate images with resolution comparable to a 128 elements array and reduced artifacts in comparison to arrays with the same number of elements.
Keywords: Genetic algorithm; Sparse array; Ultrasonic images